Sustainable Packaging Practices in Warehousing in Bulgarian Trade and Manufacturing Companies - Mihova, Lilyana (Research Papers, 2024)
Warehouse systems are an important part of the supply chain. They perform many activities that add value to the products. The purpose of this article is to show that sustainable logistics practices can be applied in packaging to reduce the harmful effects of this logistics activity on the environment. For this purpose, a survey was conducted among the Bulgarian trade and manufacturing companies. The results show the degree of application of sustainable logistics practices in packaging such as the degree of recycling of packaging, reusability and others. The conclusions made show the need to develop innovations in the field and a wider use of biodegradable and recyclable materials in packaging.